2014
DOI: 10.1080/09540253.2014.907393
|View full text |Cite
|
Sign up to set email alerts
|

Gendered educational leadership: beneath the monoglossic façade

Abstract: AcknowledgementsWith thanks to Professor Christine Skelton for her support whilst writing this paper; also to the peer reviewers whose comments have been very helpful. AbstractRecent gender retheorisation has drawn on Mikhail Bakhtin's literary and linguistic theories of monoglossia and heteroglossia to reconcile seemingly contradictory gender discourses. Thus girls/women and boys/men as they are biologically sexed might be discussed within a poststructural gender theory discourse that disconnects gender from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Further, there exist differences within the group of women interviewed. Women leaders reiterated discourses associated with both femininities and masculinities (Fuller, 2013;Priola, 2007). They inhabited a variety of identities, as evidenced by the 'Multiple', and shifted between several which were sometimes contradictory, sometimes compatible and potentially taken up to enable them to get by (Gill et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there exist differences within the group of women interviewed. Women leaders reiterated discourses associated with both femininities and masculinities (Fuller, 2013;Priola, 2007). They inhabited a variety of identities, as evidenced by the 'Multiple', and shifted between several which were sometimes contradictory, sometimes compatible and potentially taken up to enable them to get by (Gill et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These relate to ways of being in a complex, multi-faceted work /life space. This resonates with Fuller's (2014) notion of 'polyglossic simultaneity' whereby head teachers may ''switch' seamlessly between modes of doing gendered leadership depending on context & circumstances' (p321). In this study, exactness in terms of mutual exclusivity amongst emerging types is neither assumed nor implied.…”
Section: Insert Table 1-participant Data Codesmentioning
confidence: 97%
“…The research reported here is located in the first stage as documentation of the presence of women. It contextualizes research in England that has also focused on documenting women’s experiences of becoming and being head teachers (Coleman, 2002), studying women on their own terms (Fuller, 2013), women head teachers’ challenge to gendered leadership theory (Fuller, 2014a, 2015), and the transformation of leadership theory by feminist scholars such as Ozga (1993) and Adler et al (1993), who have been credited, along with Blackmore (1989), for their contribution to critical leadership studies (Grace, 2000). More recently, Helen Gunter, along with Pat Thomson and Tanya Fitzgerald, has ensured that gender shapes leadership knowledge production by focusing on identity construction (gender alongside age, disability, race and sexuality, for example); issues of social injustice (power struggles, division of labour and career paths); women’s adoption of male/masculine/masculinist and/or ‘normative’ leadership; and gender and leadership as a continuing research agenda (see Fuller, 2014b).…”
Section: Women In Secondary School Headship and The Equality Act (2010)mentioning
confidence: 99%
“…Indeed, a critical and poststructural feminist approach would be more concerned with the deconstruction of gendered power relations and the reconstruction of leadership as multidimensional and multidirectional (Blackmore, 1989, 2013). Nuanced perspectives are possible using qualitative research methods (see Fuller, 2014a, 2015). Nevertheless, this research provides a context for such research and has enabled recognition, for example, that the majority of chief executive officers of the large chains of academies are men, whilst women appeared relatively well-represented in site-based leadership (Fuller, 2016).…”
Section: The Researchmentioning
confidence: 99%
“…How feminist scholars articulate the fluidity of their standpoint has been addressed, at least in part, here. I have recognised and begun to articulate intellectual struggles with gender, feminist, and social theories and my position-taking in the field of women and gender in educational leadership (see also Fuller, 2013Fuller, , 2014b. This research has re-affirmed my position that gender is simultaneously a relational, performed and conferred identity (Adkins, 2004) that necessarily intersects with identity factors such as "race, " social class, religion, sexual orientation, nationality as well as learner, educator, leader, and scholar identities.…”
Section: Transforming a Feminist Standpointmentioning
confidence: 99%